Using cerebrospinal fluid nanopore sequencing assay to diagnose tuberculous meningitis: a retrospective cohort study in China - Lihong Zhou; Xingwu Zou; Yan Yong; Qin Hu (BMJ Open)
Objective This study aimed to evaluate the efficiency of nanopore sequencing for the early diagnosis of tuberculous meningitis (TBM) using cerebrospinal fluid and compared it with acid-fast bacilli (AFB) smear, mycobacterial growth indicator tube culture and Xpert Mycobacterium tuberculosis (MTB)/rifampicin (RIF).Design Single-centre retrospective study.Setting The Tuberculosis Diagnosis and Treatment Center of Zhejiang Chinese and Western Medicine Integrated Hospital.Participants We enrolled 64 adult patients with presumptive TBM admitted to our hospital from August 2021 to August 2023.Methods We calculated the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of AFB smear, culture, Xpert MTB/RIF and nanopore sequencing to evaluate their diagnostic efficacy compared with a composite reference standard for TBM.Results Among these 64 patients, all tested negative for TBM by AFB smear. The sensitivity, specificity, PPV and NPV were 11.11%, 100%, 100% and 32.2% for culture, 13.33%, 100%, 100% and 2.76% for Xpert MTB/RIF, and 77.78%, 100%, 100% and 65.52% for nanopore sequencing, respectively.Conclusion The diagnostic accuracy of the nanopore sequencing test was significantly higher than that of conventional testing methods used to detect TBM.